(untitled) (Journal of the College of Education for Women, 2019)
Reading strategies are of interest for what they reveal about the ways readers manage their interaction with written texts and how these strategies are related to text understanding, acquisition ,storage ,and retrieval of information .In EFL comprehension lessons, the students try to work out interpretations of the meaning related to the written word through the usage of different comprehension strategies. Yet, there are moments where the participants in the classroom fail to reach a successful understanding of the passage read despite the guidance of the teacher. The present research aims at investigating and identifying moments of comprehension failure and reasons behind them .It also aims at specifying the different strategies used in terms of type and number of occurrences. It is hypothesized that some students in EFL classrooms fail to understand parts of written texts because they do not use any kind of strategy at particular stages of the comprehension process. The samples selected for the research are the two sections of first year students in the Department of English language, College of Arts and Letters in Cihan University. Each section included 30 students who study comprehension as a basic course ,through their first academic year, in an average of 3 hours per week. Eight comprehension lessons have been recorded and the passages discussed during these lessons , were chosen from the students’ text book ‘’Practice & Progress’’ by L.G. Alexander, 1967. The research provides a brief overview of the studies related to the process of reading comprehension .It also illustrates the ways many linguists identified the factors contributing to understanding written texts during the previous years. This is followed by mentioning the general strategies that are used by learners of the English language with explanation of their meaning and role in comprehending written texts. Section two presents the analysis of the recorded lessons. Though the discussions of eight passages were recorded, only three of them were included in the research due to shortage of space. Moments of comprehension failure are specified by the letters (CF) with reference to the reason. Types of strategies used during the lessons are identified as well. Finally, it is concluded that the students sometimes fail to grasp the meaning of some lines or parts of a text because they don’t use certain strategies .The analysis of the lessons also shows that the strategies that are mostly used by the students, in their attempt to understand what they read, are: using prior knowledge, inferring meaning, questioning, visualizing, and determining importance which are used in sequence and number of occurrences that differ from one text to another .On the other hand, strategies like synthesizing and summarizing are hardly ever used in some texts and never used in others. The research also illustrates the significant role of the teacher that contributes to the students’ critical thinking and understanding of the written text